2016
DOI: 10.1080/1478422x.2016.1142161
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Halloysite nanocontainers and their compatibility with epoxy coating for anti-corrosion performance

Abstract: In this work, multi-layered Halloysite polyelectrolyte nanocontainers, which will be used to store corrosion inhibitors to develop smart coating technology, were fabricated, and doped in a homemodified epoxy coating. The Halloysite nanocontainers were characterised, and their compatibility with the epoxy coating was tested in terms of the anti-corrosion performance for X65 pipeline steel. Results demonstrate that the fabricated Halloysite nanocontainers have a more uniform scale and better dispersion than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The impedance at 0.01 Hz of unscratched coatings is found to increase with the increase in amount of halloysite loading in the epoxy coating. In general, the enhancement in corrosion protection of epoxy coating upon the addition of nanofillers is due to the improved barrier performance and better adherence of the coating to the underlying substrate . In the case of halloysite filled epoxy coating, the halloysite acts as good barrier by reducing the porosity of the epoxy coating matrix and zigzag the diffusion path available by deleterious species .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impedance at 0.01 Hz of unscratched coatings is found to increase with the increase in amount of halloysite loading in the epoxy coating. In general, the enhancement in corrosion protection of epoxy coating upon the addition of nanofillers is due to the improved barrier performance and better adherence of the coating to the underlying substrate . In the case of halloysite filled epoxy coating, the halloysite acts as good barrier by reducing the porosity of the epoxy coating matrix and zigzag the diffusion path available by deleterious species .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In general, the enhancement in corrosion protection of epoxy coating upon the addition of nanofillers is due to the improved barrier performance and better adherence of the coating to the underlying substrate. 34 In the case of halloysite filled epoxy coating, the halloysite acts as good barrier by reducing the porosity of the epoxy coating matrix and zigzag the diffusion path available by deleterious species. 35 As the amount of halloysite increases in the coating, the barrier effect increases to further enhance the corrosion protection ability of the coating.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…As the intended usage is nanocontainers, HNTs with a long, thick tubular shape are used for the smart coating (Sun et al , 2016). The layer-by-layer (LBL) method was used to increase the density of the solution and decrease shrinkage (Feng and Cheng, 2016). The deposition of polyelectrolytes was used for the storage of a heterocyclic compound with three nitrogen atoms (Feng et al , 2017), called benzotriazole (BTA) (Khiati et al , 2011), to act as a corrosion inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum phosphate (AlPO 4 ), sodium orthosilicate (Na 3 SiO 4 ), cerium salts (Ce(NO 3 ) 3 , CeCl 3 ), nickel salts (Ni(CH 3 COO) 2 , NiF 2 ) and dichromate (K 2 Cr 2 O 7 ) are common sealants used in various spraying coatings including amorphous/nanocrystalline coatings [4][5][6][7][8][9][10]. Wang et al [6] investigated the effect of sealing treatment on the corrosion behavior of high velocity oxygen fuel (HVOF) Fe-based amorphous/nanocrystalline coatings and found that sealing treatment obviously enhanced the corrosion resistance of coatings and AlPO4 sealant exhibited the best sealing effect.…”
Section: Introductionmentioning
confidence: 99%